2017
DOI: 10.3389/fmars.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of P* Reduction in the Eastern Tropical South Pacific

Abstract: Water masses influenced by oxygen minimum zones (OMZ) feature low inorganic nitrogen (N) to phosphorus (P) ratios. The surplus of P over N is thought to favor non-Redfield primary production by bloom-forming phytoplankton species. Additionally, excess phosphate (P * ) is thought to provide a niche for nitrogen fixing organisms. In order to assess the effect of low inorganic nutrient ratios on the stoichiometry and composition of primary producers, biogeochemical measurements were carried out in 2012 during a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 84 publications
(112 reference statements)
0
12
0
Order By: Relevance
“…4), indicating that they were not actively fixing N 2 at the time our study was performed. These results seem paradoxical, provided the significant N 2 fixation rates measured at these study sites (Meyer et al, 2017) and the confirmed presence of S. castanea at this site. But even if diazotrophy is a facultative trait of the presented isolate, we cannot define the extent to which the behaviour of an organism in the laboratory predicts activities in natural habitats.…”
Section: Microbial Interactions and Particle Attachmentmentioning
confidence: 77%
See 3 more Smart Citations
“…4), indicating that they were not actively fixing N 2 at the time our study was performed. These results seem paradoxical, provided the significant N 2 fixation rates measured at these study sites (Meyer et al, 2017) and the confirmed presence of S. castanea at this site. But even if diazotrophy is a facultative trait of the presented isolate, we cannot define the extent to which the behaviour of an organism in the laboratory predicts activities in natural habitats.…”
Section: Microbial Interactions and Particle Attachmentmentioning
confidence: 77%
“…Subsamples for nanoSIMS (50 ml) had been previously incubated in non‐sulfidic conditions with 15 N 2 and 13 C‐glucose for 24 hr (following Mohr et al . method and 15 N 2 supplied by Cambridge Isotopes; detailed description in Meyer et al ., ). Water samples were incubated in on‐deck incubators, which were connected to a flow‐through seawater system and were shaded with blue lagoon (Lee filters) foil to simulate light levels at the corresponding water depth.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…A detailed description of the data processing, including the calibration of oxygen can be found in Thomsen et al (2016b). As the Chl a concentrations measured by the WET Labs (USA) fluorometer did not differ significantly from Chl a concentrations determined from water samples (Meyer et al, 2017), no further calibration than the factory calibration was applied to the fluorometer data (see Loginova et al, 2016, for details). In order to obtain further subsurface hydrographic information, 53 temperature profiles organized in the two cross-frontal transects B and C with a horizontal resolution of 0.3-0.5 km were measured using the CTD sensors mounted on a microstructure profiler.…”
Section: Hydrographic and Meteorological Measurementsmentioning
confidence: 99%